ANALYSIS OF THE USE OF THE M-PISE APPLICATION IN PREVENTING CORRUPTION IN FINANCIAL MANAGEMENT AT THE BEDHA TRADITIONAL VILLAGE LPD - Adelia, Gusti Ayu Cahya; Astawa, I Gede Putu Banu; Atmaja, I Made Dwita (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The development of digital technology has encouraged Village Credit Institutions (LPD) to adapt in order to improve the transparency and accountability of financial management. The LPD of Bedha Traditional Village still faces challenges related to the misuse of funds, which has the potential to undermine public trust. This study aims to analyze the use of the M-Pise application as an effort to prevent corruption. The method used is qualitative with a descriptive approach through interviews and document studies. The results show that M-Pise is able to strengthen transparency and accountability through automatic transaction recording and digital features, including interbank transfers, QRIS payments, digital archives, and real-time access to savings balances. This application has been proven to reduce opportunities for data manipulation and financial abuse, while increasing public trust in LPDs. This study contributes to the literature on the digitization of local financial institutions and provides practical recommendations for strengthening technology-based fund management systems in the LPD environment.